Nursing Students' Experiences Towards Using ChatGPT as a Teaching Tool: A Descriptive Qualitative Study - Karaçay, Pelin; Yaşar, Özgen (Teaching and learning in nursing, 2025)
•Studies investigating the effect of using ChatGPT as a teaching tool in nursing education are limited in the literature.•Nursing students’ use of generative artificial intelligence tools such as ChatGPT in education is inevitable. Therefore, nurse educators can guide students by using ChatGPT as a teaching tool in nursing education.•This study may guide nursing educators on the appropriate use of AI tools like ChatGPT as a teaching tool in the classroom and contribute to the ethical and responsible use of such tools in higher education. Nowadays, nursing students’ use of generative artificial intelligence tools such as ChatGPT in education is inevitable. Therefore, nurse educators can guide students using ChatGPT as a teaching tool. Studies investigating ChatGPT as a teaching tool in nursing education are very limited in the literature. This study aimed to reveal sophomore nursing students' experiences and perspectives toward ChatGPT activities used as a teaching tool in the classroom. The study used a descriptive qualitative design and a researcher-developed survey. The study sample consisted of 24 sophomore nursing students who participated in ChatGPT activities in the classroom and agreed to participate in the survey. Data were analyzed by using descriptive thematic analysis. Classroom ChatGPT activities improved the participants' knowledge of the subject matter and their knowledge of the ChatGPT application. These activities also promoted critical thinking and increased awareness regarding the use of artificial intelligence tools among the participants. In-class ChatGPT activities can enhance nursing students' knowledge of the subject and the ChatGPT application and provide them with a critical perspective.